Aetiology of growth hormone deficiency. Issue 7 (July 1987) - Herber, S M; Kay, R
Abstract : A retrospective analysis was performed in an attempt to identify perinatal risk factors for the development of growth hormone deficiency. More of the affected children were boys, and their birth weights were significantly lower than those of the national average; there were also considerably more preterm and post-term deliveries among boys.